Biodistribution and dosimetry of 195mPt-cisplatin in normal volunteers - Sathekge, M.; Wagener, J.; Smith, S. V.; Soni, N.; Marjanovic-Painter, B.; Zinn, C.; Van de Wiele, C.; D’Asseler, Y.; Perkins, G.; Zeevaart, J. R. (Nuklearmedizin - NuclearMedicine, 2013)
195mPt-cisplatin is regarded as a promising imaging agent for optimizing dosage in patients receiving cisplatin chemotherapy. Methods: We investigated the whole-body distribution and radiation dosimetry of 195mPt-cisplatin in humans. Whole-body scans were obtained up to 144 h after intravenous injection of 112.4 MBq 195mPt-cisplatin in each of five subjects. Blood samples were taken at various times up to 144 h after injection. Urine was collected up to 114 h after injection for calculation of renal clearance and whole-body clearance. Time/activity curves were generated by fitting the organ-specific geometric mean counts, obtained from regions of interest, on the respective images as a function of the time after injection. OLINDA software package was applied to calculate the absorbed radiation dose for various organs. Results: Most of the activity (32 ± 4%) was excreted in the urine during the first 5 h. The effective clearance half-life derived from extrapolation of the whole-body curve was 40 hours (1.7 days). On average, the highest dose was received by the kidneys (mean dose received 2.68 ± 1.5 mGy/MBq), followed by the spleen (mean dose received 1.6 ± 0.8 mGy/MBq) followed by the liver (mean dose received 1.45 ± 0.38 mGy/MBq). The estimated mean effective dose for the adult subject was 0.185 ± 0.034 mSv/MBq. Conclusion: 195mPt-cisplatin proved a safe radiopharmaceutical with a favourable bio distribution for early and delayed imaging of pathology above the diaphragm. The ED obtained was 0.185 ± 0.034 mSv/MBq. The highest organ dose was received by the kidneys (2.68 ± 1.5 mGy/ MBq).
Keywords: 195mPt-cisplatin; normal volunteers; bio-distribution